IMPROVING LISTENING COMPREHENSION BY USING ENGLISH SONGS FOR THE TENTH-GRADE STUDENTS AT SMAN 10 GOWA - Jamila; Muliaty Ibrahim; Suharti Siradjuddin (PT PUBLIKASI INSPIRASI INDONESIA, 2023)
Listening is one of the four most essential English learning skills students have in learning. The research objective was to improve students' listening skills through the use of English songs. This study used a quantitative type of experimental method. There were two classes, namely the experimental class with English songs and the control class without English songs. The research sample was grade X students consisting of 50 students in which 25 students in each experimental class and control class. Data collection techniques in this study used a pre-test and post-test. The results showed that the pre-test for the experimental class had a mean value of 57.88 and the pre-test for the control class had a mean value of 55.04. Then, after treatment, the research results showed that the experimental class post-test had a mean value of 86.08 and the control class post-test had a mean value of 73.00. The results of the data were analyzed by using an independent T-test showing that Sig. (2-tailed) is 0.000 which is lower than 0.05 so that (Ha) is accepted and (Ho) is rejected so that there is an influence on listening results of using English songs. Based on the research results, it can be concluded that English songs can improve listening skills for grade X of SMAN 10 Gowa.